Puréed Foods for Swallowing Problems - Wendy J. Dahl (EDIS)
Puréed foods are prepared by mashing, grinding, or chopping food until a very fine, smooth texture is achieved. Mashed potatoes, squash, and pumpkin pie filling are examples of puréed foods. Although we all enjoy puréed foods as a part of a healthy diet, puréed diets may be recommended for frail older adults who have chewing and/or swallowing problems. This 3-page fact sheet describes reasons to prepare puréed foods and tips for preparing and serving great tasting and ready to swallow puréed foods. Written by Wendy J. Dahl and published by the UF Department of Food Science and Human Nutrition, March 2011.